Avaliação das alterações no sistema somatossensorial como estratégia para o diagnóstico precoce e tratamento de pacientes com transtorno do espectro autista - TEA - SANTA MARIA, Bruna Castro (Universidade Federal do Pará, 2021)
Autism spectrum disorder (ASD) is characterized by persistent deficits in communication and social interaction in multiple contexts and restricted and repetitive patterns of behavior, interests or activities. The most recent edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), presented the addition of "hyper and hypo-reactivity to sensory input or unusual interests in sensory aspects of the environment" as defining diagnostic characteristics of autism. Individuals with autism often report tactile sensitivities, such as stiffness or withdrawal when touched. Thus, the objective of this study was to identify changes in somesthetic sensitivity that may assist in strategies for early diagnosis and intervention of patients with autism. Clinical observations and questionnaires were carried out among the participants, where it was observed that children from control group showed minimal alterations in somesthetic reactivity when compared with the ASD group. It was found that 90% of the participants in the TEA group did not play with different consistencies; 70% do not play with gelatinous objects and materials of different textures, as well as showing an aversion to certain fabrics and / or clothing labels; 62% do not participate in games that get wet or smeared and walk or walked on tiptoe and 50% avoid hugging and / or physical contact, showing that in children with autism it is possible to notice early hypo or somesthetic hyperreactivity, which could support the diagnosis and early intervention strategies.